Peran Artificial Intelligence dan Good Corporate Governance terhadap Manipulasi Laba di Era Digital - Melia Jaya Puspa Rini; Maysarla Anggun Azzahra; Fika Nur Amalia; Dien Noviany Rahmatika (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
Earnings manipulation remains a major issue in financial reporting as it can reduce information quality and mislead stakeholders. The development of the digital era has encouraged the utilization of Artificial Intelligence (AI) and the implementation of Good Corporate Governance (GCG) as strategic mechanisms to minimize earnings manipulation practices. This study aims to examine the role of Artificial Intelligence and Good Corporate Governance in mitigating earnings manipulation in the digital era. The research employs a Systematic Literature Review (SLR) method by analyzing 21 national and international journal articles published between 2020 and 2026. The findings indicate that the implementation of Artificial Intelligence can enhance the quality of financial statements through anomaly detection, real-time data analysis, and the identification of patterns that are not detectable using traditional methods. Good Corporate Governance, through mechanisms such as independent boards of commissioners, audit committees, institutional ownership, managerial ownership, and audit quality, plays a significant role in strengthening oversight and limiting managerial discretion in engaging in earnings manipulation. Overall, the results suggest that Artificial Intelligence and Good Corporate Governance constitute effective approaches to improving transparency, integrity, and credibility of corporate financial reporting in the digital era.